Atribuições dos conselhos municipais de educação da mesorregião centro maranhense: destaques e enfoques nas leis dos CMEs - SANTOS, Regiane Andrade dos (2020)
This research is linked to the line of research History and Education Policies, linked to the research group “Educational Management Policy and Human Training” whose axis deals with Management and organization of education systems and councils, aimed at analyzing how the functions and attributions in the legal instruments that guide the functioning of the Municipal Councils of Education (CMEs) in Mesoregion Centro Maranhão, from the perspective of democratic management. For that, the qualitative approach was used, through the following procedures: bibliographic research, to understand definitions and concepts of the themes and categories that forward the object; and documentary, through the evidenced laws - Laws for the Creation of Municipal Education Systems (SMEs), the Laws of CMEs and the Internal Regulations of the municipalities of Arame, Bom Lugar, Grajaú, Lago Verde and São Luís Gonzaga do Maranhão, from content analysis, as indicated by Bardin (1998). In the first moment, the historical and legal milestones of the Education Councils in Brazil were approached, based on Cury (2006), Bordignon (2009), Farias (2012), Ferreira and Ferreira (2013), Gohn (2011), Lima ( 2012), Marcelino (2013), among others, in order to understand the management of educational policies in municipalities, was based on the following categories: participation, autonomy and representation. In the second moment, it was discussed about federalism in Brazil, with a view to understanding the process of decentralization and autonomy, as well as the municipalities and federative issues after the Federal Constitution of 1988, the SME and the collaboration regime, based on the studies by Abrucio (2010), Cury (2010), Arretche (2004), Almeida (2001), Sousa (2015), Souza (2005). In the third moment, the functions and attributions of the CMEs for the management of municipal education were analyzed, highlighting social control in the definition of educational policies. The composition of the councils, the definition of the nature of the body, as well as the analysis of the laws of the councils based on the composition, functions and attributions were also emphasized. It was concluded that the CME is an instrument for the democratization of educational policies, which have in their legislation the legal conditions for the materialization of municipal management. The CMEs of the municipalities of Arame, Bom Lugar, Grajaú, Lago Verde and Luís Gonzaga do Maranhão have a plural composition, that is, their representatives are formed by different representatives: parents, teachers, education technicians, secretaries and others. It was observed that the consultative, deliberative, normative, propositional, supervisory functions were identified in the legislation of the CMEs. It was also noticed that in the legislation of the WECs of Arame, Lago Verde and Grajaú analyzed, omission of information was detected, with regard to the origin of the members (if they come from the Municipal Executive or from civil society), which made it impossible to classify as to the nature of the organ. It was also found that only two municipalities present such information in the laws that create the CMEs, those of Bom Lugar and São Luís Gonzaga do Maranhão, present characteristics, from the legal point of view, as a State body.